PENGEMBANGAN E-MODUL BERDIFERENSIASI TERINTEGRASI KOMPETENSI SOSIAL EMOSIONAL UNTUK MENINGKATKAN KEMAMPUAN BERNALAR KRITIS DAN KEMAMPUAN KOLABORATIF - ASTUTHI, YULYA (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2024)
Critical and collaborative reasoning skills are important skills that students must have in the era of globalization. These skills are part of the Pancasila student profile and 21st century skills 6C. The results of observations, interviews, questionnaires, and tests show that these two skills are still low in students. This is due to the lack of fulfillment of learning needs due to the unavailability of appropriate learning designs. This study aims to develop a mathematics e-module based on integrated differentiated learning with social-emotional competencies to improve the critical and collaborative reasoning skills of grade 5 students on the material of the area of ??rectangular flat shapes. The study used the ADDIE model with subjects of grade 5 students of UPT SD Negeri 15 Gresik. The research instruments included expert validation, student and teacher response questionnaires, pre-tests and post-tests to test critical reasoning skills, and observations to test collaborative skills. The e-module was developed using Canva for Education and designed in accordance with the independent curriculum, integrating differentiated learning and social-emotional competencies. The results of the study showed that the e-module was declared valid by material experts, media, and education practitioners with percentages of 95.67%, 94.07%, and 94.9%, respectively. The practicality of the module was declared very high with a score of 99.7% from students and 98% from teachers. The increase in students' critical reasoning skills was 39.4 points with an average score of 93.8, exceeding the KKTP score. The effectiveness test showed an N-Gain value of 0.8767 (high category). Collaborative skills increased by 27% with an average score of 94. This e-module is proven to be valid, practical, and effective in supporting learning. ABSTRAKKemampuan bernalar kritis dan kolaboratif merupakan keterampilan penting yang harus dimiliki siswa di era globalisasi. Kemampuan ini merupakan bagian dari profil pelajar Pancasila dan keterampilan abad 21 6C. Hasil observasi, wawancara, angket, dan tes menunjukkan bahwa kedua kemampuan ini masih rendah pada siswa. Hal ini disebabkan oleh kurangnya pemenuhan kebutuhan belajar akibat tidak tersedianya rancangan pembelajaran yang tepat. Penelitian ini bertujuan mengembangkan e-modul matematika berbasis pembelajaran berdiferensiasi terintegrasi dengan kompetensi social emosional untuk meningkatkan kemampuan bernalar kritis dan kolaboratif siswa kelas 5 pada materi luas bangun datar persegi panjang. Penelitian menggunakan model ADDIE dengan subjek siswa kelas 5 UPT SD Negeri 15 Gresik. Instrumen penelitian meliputi validasi ahli, angket respon siswa dan guru, pre-test dan post-test untuk menguji kemampuan bernalar kritis, dan observasi untuk menguji kemampuan kolaboratif. E-modul dikembangkan menggunakan Canva for Education dan dirancang sesuai dengan kurikulum merdeka, mengintegrasikan pembelajaran berdiferensiasi serta kompetensi sosial-emosional. Hasil penelitian menunjukkan e-modul dinyatakan valid oleh ahli materi, media, dan praktisi pendidikan dengan persentase berturut-turut 95,67%, 94,07%, dan 94,9%. Kepraktisan modul dinyatakan sangat tinggi dengan skor 99,7% dari siswa dan 98% dari guru. Peningkatan kemampuan bernalar kritis siswa sebesar 39,4 poin dengan nilai rata-rata 93,8, melampaui nilai KKTP. Uji efektivitas menunjukkan nilai N-Gain 0,8767 (kategori tinggi). Kemampuan kolaboratif meningkat sebesar 27% dengan nilai rata-rata 94. E-modul ini terbukti valid, praktis, dan efektif dalam mendukung pembelajaran.